2023
DOI: 10.3389/fpsyg.2023.1009459
|View full text |Cite
|
Sign up to set email alerts
|

A managers’ work engagement framework for the digital tasks

Abstract: Unlike much research on work engagement, there is not much literature focused on managers that discuss their job demands and resources related to digital challenges in today’s organizations. Grounded in the JD-R model and considering the current digital world context, we build four research propositions and offer a work engagement framework that considers the boundary conditions of digital managerial tasks. Our conceptual framework relates the new job demands and resources to digital managerial tasks: digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 81 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Conceptually, mediation assumes a causal and longitudinal process involving three causal relationships (Kenny et al, 2003). In this paper, I argue that digital work characteristics (X) (Parker and Grote, 2022), that is, the digital-related demands and resources (Bakker and Demerouti, 2017), correlate strongly with individual results, such as the task performance (Y) (Juyumaya and Torres, 2023b). However, I may suspect that a third variable makes this correlation possible through a relationship between these constructs because digital work characteristics, being a characteristic of the organization, is a variable somewhat distant from individual thought (e.g.…”
Section: Framework Developmentmentioning
confidence: 99%
“…Conceptually, mediation assumes a causal and longitudinal process involving three causal relationships (Kenny et al, 2003). In this paper, I argue that digital work characteristics (X) (Parker and Grote, 2022), that is, the digital-related demands and resources (Bakker and Demerouti, 2017), correlate strongly with individual results, such as the task performance (Y) (Juyumaya and Torres, 2023b). However, I may suspect that a third variable makes this correlation possible through a relationship between these constructs because digital work characteristics, being a characteristic of the organization, is a variable somewhat distant from individual thought (e.g.…”
Section: Framework Developmentmentioning
confidence: 99%
“…Finally, the findings complement the scarce stream of literature on technology reflectiveness (Golgeci et al , 2022; Schweitzer et al , 2015). Past studies have revealed that technological reflectiveness plays an important role in facilitating various desirable outcomes, such as environmental innovation (Golgeci et al , 2022), social innovation (Schweitzer et al , 2015), intentions to accept a new technology (Andrade-Valbuena and Torres, 2018) and work engagement (Juyumaya and Torres, 2023). The current study extents the concept to the marketing domain and helps reveal the role technology reflectiveness plays in facilitating co-creation processes between brands and their customers.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Furthermore, this form of leadership emphasizes the ability to inspire and guide teams, fostering a culture of innovation and collaboration essential for digital transformation ( Koponen et al, 2023 ). Beyond affecting managerial roles, the digital revolution has profound implications for employee work engagement ( Juyumaya and Torres, 2023 ). Digital technologies alter the work environment, task structures, and communication channels, leading to shifts in employee roles, expectations, and engagement levels ( Toth et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%